PEREMPUAN MINANGKABAU DALAM KARYA LUKIS DEKORATIF - JULIUS HADE PUTRA, Drs. Abd. Hafiz, M.Pd, Drs. Erfahmi, M.Sn. (Universitas Negeri Padang, 2015)
The purpose of this last work is visualize women of Minangkabau in the work of decorative art, to reach comprehension about women of Minangkabau position that have and should be a example. Realization of decorative art is dominate of elementshape and colour like a simplify shape objeck with distortion by acrilyk at canvas on decorative design. This metode and step in process of making work began from preparations, elaboration, synthetic, realization consep until present to publick with exhibition. This last work give information to people enjoying the work art about the valve that in women Minangkabau position is very much and safelly by culture, this describable in tens themes work of decorative art.Kata Kunci: women, Minangkabau, Art, Dekorative